Concentration and isotopic composition of atmospheric N2O over the last century ... - Ahn, Jinho; Buizert, Christo; Etheridge, David; Ghosh, Sambit; Joong Kim, Seong; Langenfelds, Ray L; Toyoda, Sakae; Yoshida, Naohiro (U.S. Antarctic Program (USAP) Data Center, 2023)
We have reconstructed the atmospheric N2O mole fraction and its isotopic composition by combining data from ice cores, firn air, and atmospheric samples. The mole fraction reconstruction extends back to 1000 CE using ice cores, firn air, and atmospheric sampling; and the isotopic reconstruction extends back to 1900 CE using only firn air data. We have incorporated both newly measured and previously published data. We present new data for the mole fraction, d15Nbulk, d18O, and d15NSP values from the Styx (East Antarctica) firn air, and mole fraction from the North Greenland Eemian Ice drilling Project (NEEM) firn air. We have used published records from the Styx and NEEM ice cores, direct atmospheric measurements from the NOAA global sampling network, and firn air data, giving a total of 11 sites for N2O mole fraction, 12 sites for d15Nbulk, 11 sites for d18O, and 8 sites for d15NSP values. ...